2020
DOI: 10.1093/tas/txaa166
|View full text |Cite
|
Sign up to set email alerts
|

Cow efficiency: modeling the biological and economic output of a Michigan beef herd

Abstract: In recent decades, beef cattle producers have selected cattle for biological traits (ie. improved growth) to maximize revenue, leading to an increase in average cow body size. However, matching cow size to the production environment would allow producers to maximize productivity and economic returns per unit of land. This may help meet the goals of sustainable intensification, but environmental complexity and varying cow-calf production systems dictates a regional approach. The objective of this experiment was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…Weiterhin wurde in den letzten Jahren mehrfach nachgewiesen, dass größerrahmige Tiere nicht wie vermutet 58 produktiver sind, sondern dass Körpergewicht und Körpergröße negativ mit der Effizienz der Futterausnutzung und Reproduktion korrelieren 59 60 61 . Die Hinterwälder kommen auch aus diesen Gründen dem Ideal der optimalen Produktivität in einer nachhaltigen Rinderhaltung sehr nahe.…”
Section: Diskussionunclassified
“…Weiterhin wurde in den letzten Jahren mehrfach nachgewiesen, dass größerrahmige Tiere nicht wie vermutet 58 produktiver sind, sondern dass Körpergewicht und Körpergröße negativ mit der Effizienz der Futterausnutzung und Reproduktion korrelieren 59 60 61 . Die Hinterwälder kommen auch aus diesen Gründen dem Ideal der optimalen Produktivität in einer nachhaltigen Rinderhaltung sehr nahe.…”
Section: Diskussionunclassified
“…Household survey data were predominantly used for classification of livestock production at national and sub-national level. Databases used to establish livestock classification systems include FAOSTAT, the FAO's Gridded Livestock of the World, The Livestock Marketing Information Centre, the Australian Bureau of Agricultural and Resource Economics and Sciences, the Australian Bureau of Statistics (2020), and the Agriculture and Australian Lot Feeders Association (Vigre et al, 2016;Shapiro et al, 2017; Food and Agriculture Organization of the United Nations, 2018; van Hal et al, 2019;Thompson et al, 2020;Fordyce et al, 2021) (Appendix 1, Table 4).…”
Section: The Datasets and Spatial Resolutions Of Pre-existing Classif...mentioning
confidence: 99%
“…The biological and economic output efficiency is very important for dairy farmers, and it has been reported that lighter cows provide a comparatively higher economic value based on land ( Thompson et al, 2020 ). It has also been reported that feed efficiency (milk yield per kg feed) was negatively correlated, ranging from −0.18 for wither height to −0.33 for body weight, with body weight and the body measurements ranging from −0.18 for wither height to −0.33 for body weight ( Sieber et al, 1988 ).…”
Section: Introductionmentioning
confidence: 99%